Recombinant Anti-PF4 Antibodies Derived from Patients with Vaccine-Induced Immune Thrombocytopenia and Thrombosis (VITT) Facilitate Research and Laboratory Diagnosis of VITT - Luisa Müller; Venkata A. S. Dabbiru; Lucy Rutten; Rinke Bos; Roland Zahn; Stefan Handtke; Thomas Thiele; Marta Palicio; Olga Esteban; Marta Broto; Tom Paul Gordon; Andreas Greinacher; et al. (Vaccines)
Background/Objectives: Adenoviral vector-based vaccines against COVID-19 rarely cause vaccine-induced immune thrombocytopenia and thrombosis (VITT), a severe adverse reaction caused by IgG antibodies against platelet factor 4 (PF4). To study VITT, patient samples are crucial but have become a scarce resource. Recombinant antibodies (rAbs) derived from VITT patient characteristic amino acid sequences of anti-PF4 IgG are an alternative to study VITT pathophysiology. Methods: Amino acid sequences of the variable region of immunoglobulin light and heavy chain of anti-PF4 IgG derived from VITT patients were obtained by mass spectrometry sequencing and rAbs were synthetized by reverse-engineering. Six different rAbs were produced: CR23003, CR23004, and CR23005 (from a patient vaccinated with Jcovden, Johnson & Johnson-Janssen (Beerse, Belgium)), CR22046, and CR22050 and CR22066 (from two different patients vaccinated with Vaxzevria, AstraZeneca (Cambridge, UK)). These rAbs were further characterized using anti-PF4 and anti-PF4/heparin IgG ELISAs, rapid anti-PF4 and anti-PF4/polyanion chemiluminescence assays, and PF4-induced platelet activation assay (PIPA) and their capacity to induce procoagulant platelets. Results: rAbs bound to PF4 alone, but not to PF4/polyanion complexes in rapid chemiluminescence assays. Chemiluminescence assays and both anti-PF4 IgG and anti-PF4 IgG/heparin ELISA showed concentration-dependent PF4 binding of all six rAbs, however, with different reactivities among them. PIPA showed a similar, concentration-dependent platelet activation pattern. rAbs varied in their reactivity and the majority of the tested rAbs were able to induce procoagulant platelets. Conclusions: The six rAbs derived from VITT patients reflect VITT-typical binding capacities and the ability to activate platelets. Therefore, these rAbs offer an attractive new option to study VITT pathophysiology.